Immunological and laboratory features of HIV infection in infants of the first year of life - V. N. Timchenko; Yu. A. Arkhipova; N. D. Dzhangavadze (Журнал инфектологии)
To study the characteristics of laboratory tests of infants born to HIV-positive women and left without parental care in the dynamics analyzed blood samples using methods of immunological and serological diagnosis of HIV infection, the qualitative and quantitative determination of HIV, as well as clinical blood analysis and screening for prenatal infection. There are informative PCR diagnostics of perinatal HIV infection in the first months of life, ELISA and western blot from the age of 9 months. Identified difference performance of a specific red blood cell and leukocyte parts of blood of hemogram in infants with perinatal HIV infection compared with those in not infected infants. Improvement in laboratory parameters is the result of appointment of HAART (highly active antiretroviral therapy).